(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents an economic-geographic analysis of the investment potential of the Fergana economic region and provides a systematic exposition of its developmental factors. The study evaluates key determinants such as the region’s demographic situation, production infrastructure, resource distribution, and inflow of foreign investments. Based on empirical data, the research analyzes changes in statistical indicators related to gross regional product and the volume of investments in fixed capital for the period 2014–2023, as well as the dynamics of growth in the number of enterprises with foreign investment participation. In addition, the study assesses the impact of investment disparities, demographic pressure, resource constraints, and the uneven development of industrial sectors on regional stability. The authors propose a set of comprehensive strategic measures aimed at enhancing the investment potential of the Fergana economic region.